(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article describes the importance of increasing the effectiveness of Arabic language classes based on the use of modern pedagogical technologies, in particular, the importance of boomerang technology in explaining Arabic grammatical rules, and the ways and instructions for its use